Model Implementasi Program Pengentasan Kemiskinan Di Kabupaten Lamongan (Implementation Model of Poverty Awakeness Program in Lamongan Region) - Achmad Syafi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2013)
Poverty reduction in Lamongan Regency is part of the policy priorities and part of the implementation of development in Indonesia. Operationally, implementation of policies to reduce poverty in Lamongan manifested in a variety of empowerment programs that centered on Badan Pemberdayaan Masyarakat (Bapemas). Considering the geographic and demographic conditions of Lamongan, the real problem of poverty is similar to other Regencys in East Java. The poor community are not only concentrated in urban communities but also scattered throughout the Lamongan regency, both in urban, rural and coast. Three of them require the different approaches of empowerment for the poor community programs and policy models. In this research focused on the implementation of poverty reduction programs in the regency Lamongan to determine model which used to avchieve success of poverty reduction with a qualitative approach. The results of research showed that the successful implementation of poverty reduction programs in Lamongan because of good communication between the implementor, the optimal use of resources, an attitude that is committed, an organized institutionalization, appropriate standards and targets as well as attention to social conditions of political. That success can be seen from the dimensions of economic empowerment, educational empowerment dimensions and the dimensions of empowerment participation. Depart from the reality of the results of this study, empowerment of the poor community in Lamongan Regency is done based onÂ basic potential of poor community and always pay attention to local knowledge which integrated with synergistic programs among the institutions that touch the poor community to become independent. Key words: Awakeness of the poor